Effects of ammonia-N stress on the antioxidant enzymes, heat shock proteins, and apoptosis-related genes of Macrobrachium rosenbergii. Issue 1 (1st January 2021) - Dong, Xuexing; Liu, Qigen; Zhao, Weihong; Ou, Jiangtao; Jiang, FengJuan; Guo, Haisong; Lv, Linlan
Abstract: Current study explored the acute toxicity and oxidative stress of ammonia-N on Macrobrachium rosenbergii. Prawns were exposed to ammonia-N at 3.01, 3.55, 4.18, 4.92, 5.80, 6.82, and 8.04 mg·L −1 for a 96 h acute toxicity test. In the subsequent sublethal toxicity text, they were exposed to ammonia-N at 0.5 or 1.88 mg·L −1 (1/2 96 h LC50) for 3, 8, 12, 24, 48, and 72 h. The total superoxide dismutase (T-SOD) activity, catalase (CAT) activity and malondialdehyde (MDA) content were detected in the muscle, haemolymph, and gill. The gene expression of antioxidases ( Cu/ZnSOD, CAT, GPX ), heat shock proteins ( HSP60, HSP70, HSP90 ), and apoptosis-related genes ( Caspase 3, Bok ) in the muscle and hepatopancreas also was evaluated. The LC50 values of non-ionic ammonia at 24, 48, 72, and 96 h were 7.72, 5.44, 4.28, and 3.78 mg·L −1, respectively. Ammonia-N significantly affected the T-SOD and CAT activities in the haemolymph and gill but not in the muscle. After 72 h of ammonia-N exposure, MDA content in the muscle, haemolymph, and gill in 1.88 mg·L −1 group significantly increased. The relative mRNA expression of antioxidant enzymes, heat shock proteins and Caspase 3 were upregulated in the hepatopancreas and muscle after ammonia exposure, especially in 1.88 mg·L −1 . This result suggested that 1/2 96 h LC50 ammonia exposure induced severe oxidative stress, eventually even apoptosis of M. rosenbergii through the caspase pathway. Highlights: Half of 96 h LC50 ammonia-N caused severe oxidative stress on M. rosenbergii. Ammonia-N induced the antioxidase and HSP to protect cells from oxidative stress. Ammonia-N induced mRNA expression level of Caspase 3 of M. rosenbergii .